Visualizing band structure hybridization and superlattice effects in twisted MoS2/WS2 heterobilayers. (21st December 2021) - Jones, Alfred J H; Muzzio, Ryan; Pakdel, Sahar; Biswas, Deepnarayan; Curcio, Davide; Lanatà, Nicola; Hofmann, Philip; McCreary, Kathleen M; Jonker, Berend T; Watanabe, Kenji; Taniguchi, Takashi; Singh, Simranjeet; et al.
Abstract: A mismatch of atomic registries between single-layer transition metal dichalcogenides (TMDs) in a two-dimensional (2D) van der Waals heterostructure produces a moiré superlattice with a periodic potential, which can be fine-tuned by introducing a twist angle between the materials. This approach is promising both for controlling the interactions between the TMDs and for engineering their electronic band structures, yet direct observation of the changes to the electronic structure introduced with varying twist angle has so far been missing. Here, we probe heterobilayers comprised of single-layer MoS2 and WS2 with twist angles ranging from 2 ∘ to 20 ∘ and determine the twist angle-dependent evolution of the electronic band structure using micro-focused angle-resolved photoemission spectroscopy. We find strong interlayer hybridization between MoS2 and WS2 electronic states at the Γ ˉ -point of the Brillouin zone, leading to a shift of the valence band maximum in the heterostructure. Replicas of the hybridized states are observed at the center of twist angle-dependent moiré mini Brillouin zones. We confirm that these replica features arise from the inherent moiré potential by comparing our experimental observations with density functional theory calculations of the superlattice dispersion. Our direct visualization of these features underscores the potential of using twisted heterobilayer semiconductors to engineer hybrid electronic states and superlattices that alter the electronic and optical properties of 2D heterostructures for a wide range of twist angles.